Transcriptome Analysis Reveals the Complex Molecular Mechanisms of Brassica napus–Sclerotinia sclerotiorum Interactions - Xu, Binjie; Gong, Xi; Chen, Song; Hu, Maolong; Zhang, Jiefu; Peng, Qi (Frontiers in Plant Science, 2021)
Sclerotinia stem rot caused by Sclerotinia sclerotiorum is a devastating disease for many important crops worldwide, including Brassica napus. Although numerous studies have been performed on the gene expression changes in B. napus and S. sclerotiorum, knowledge regarding the molecular mechanisms of B. napus–S. sclerotiorum interactions is limited. Here, we revealed the changes in the gene expression and related pathways in both B. napus and S. sclerotiorum during the sclerotinia stem rot (SSR) infection process using transcriptome analyses. In total, 1,986, 2,217, and 16,079 differentially expressed genes (DEGs) were identified in B. napus at 6, 24, and 48 h post-inoculation, respectively, whereas 1,511, 1,208, and 2,051 DEGs, respectively, were identified in S. sclerotiorum. The gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses showed that most of the hormone-signaling pathways in B. napus were enriched, and thus, the hormone contents at four stages were measured. The DEGs and hormone contents revealed that salicylic acid was activated, while the jasmonic acid pathway was repressed at 24 h post-inoculation. Additionally, the expressional patterns of the cell wall-degrading enzyme-encoding genes in S. sclerotiorum and the hydrolytic enzymes in B. napus were consistent with the SSR infection process. The results contribute to a better understanding of the interactions between B. napus and S. sclerotiorum and the development of future preventive measures against SSR.